When the body speaks of loss: psychosomatic dysregulation as a mediator between insecure attachment and prolonged grief symptoms in oncological and traumatic bereavement - Lenzo, Vittorio; Triscari, Sergio; Quattropani, Maria C.; Bordino, Valentina; Cibelli, Filomena; Lombardo, Luigi; Caretti, Vincenzo; Schimmenti, Adriano; Sideli, Lucia (Frontiers in Psychology, 2025)
BackgroundThis study investigated the role of psychosomatic dysregulation as a mediating factor in the association between attachment insecurity and prolonged grief symptoms.MethodsA cross-sectional design was used to survey 227 adults who had lost a loved one due to oncological (n = 138) or traumatic causes (n = 89) (74.0% female; age = 48.11 ± 11.53 years). The two groups did not differ significantly in terms of age, gender, marital status, or living arrangement. Participants completed the relationship questionnaire, the psychosomatic dysregulation inventory, and the traumatic grief inventory SR +.ResultsThe severity of prolonged grief symptoms did not significantly differ between groups, although participants in the oncological loss group reported slightly higher symptom severity compared to the traumatic loss group. The prevalence of probable PGD was similar between groups, with 13.8% of the oncological group and 10.1% of the traumatic group meeting diagnostic criteria. Results of mediation analysis showed that psychosomatic dysregulation partially mediated the relationship between attachment anxiety and prolonged grief symptoms, whereas no significant mediation was observed for attachment avoidance.DiscussionThese findings point out the importance of addressing psychosomatic processes in individuals with high attachment anxiety, in line with the hyperactivation model of the anxious attachment system, to better understand and support their grief responses.